PENGENDALIAN PERSEDIAAN DAN PENJADWALAN PASOKAN BAHAN BAKU IMPORT DENGAN METODE ABC ANALYSIS DI PT UNILEVER INDONESIA, CIKARANG, JAWA BARAT - Happy Fauzi Afianti; Hery Hamdi Azwir (Jurnal IPTEK, 2017)
Inventory control becomes a very important activity in a company because the cost of inventory can reach about 20% to 40% of the total annual value. Inventory is a capital or company asset consist of raw materials, work in process and finished product. Currently, the value of inventory at PT Unilever Indonesia Savory Factory has exceeded the maximum target of the company but some raw materials have shortage or stock-out, meaning that the current inventory condition is inefficient because the company invests too much in inventory but the shortage of inventory for certain raw materials still occurs. This is the reason why it is necessary to improve inventory efficiency. Improvements were made by utilizing ABC inventory analysis method and arranging and scheduling raw material supply as needed, then making priority scale of raw material improvement on ABC inventory analysis based on class A, B and C. The research was continued by rescheduling the tracking delivery and counting time frozen horizon which is the amount of time it takes raw materials during the distribution process or delivery process, so the frozen horizon is smaller than lead time. By performing fixed order interval on class A and fixed order quantity raw materials for class B and C raw materials, the quantity of imported raw materials gradually adjust to the needs and the high value of the company’s inventory can be reduced gradually as well. The end result is the risk of shortage can be reduced as much as 26%, overstock can be reduced by 12% and in total overall value over value inventory can be decreased as much as 23%.